2022
DOI: 10.3389/fmicb.2022.1020147
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analysis of hepatitis B virus before and during long-term therapy in chronic infected patients: Molecular characterization, impact on treatment and liver disease progression

Abstract: Hepatitis B virus (HBV) infection remains a serious public health concern worldwide despite the availability of an efficient vaccine and the major improvements in antiviral treatments. The aim of the present study is to analyze the mutational profile of the HBV whole genome in ETV non-responder chronic HBV patients, in order to investigate antiviral drug resistance, immune escape, and liver disease progression to Liver Cirrhosis (LC) or Hepatocellular Carcinoma (HCC). Blood samples were collected from five chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 147 publications
0
1
0
Order By: Relevance
“…Table 3 illustrates that the HBV genotype does not seem to have a substantial impact on the clinical manifestations of hepatitis B patients [ 65 ]. Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…Table 3 illustrates that the HBV genotype does not seem to have a substantial impact on the clinical manifestations of hepatitis B patients [ 65 ]. Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ].…”
Section: Prognostic Markersmentioning
confidence: 99%